Forced convection three-dimensional Maxwell nanofluid flow due to bidirectional movement of sheet with zero mass flux. (June 2022) - Ahmad, Manzoor; El-Zahar, Essam Rashdy; Al-Khaled, Kamel; Rasheed, Mehwish; Khan, Sami Ullah; Taj, Muhammad; Khan, M. Ijaz; Elattar, Samia
Abstract: The 3D mixed convection flow of Maxwell nanofluid is investigated in this paper. A stretching surface in two adjacent directions causes the flow. The temperature and nanoparticle concentration distribution are explored using the Buongiorno framework for nanofluid and thermophoresis impacts and Brownian motion. Introducing dimensionless variables and boundary layer approximations the governing PDEs are reduced to set of nonlinear ODEs. Developed system of equations then solved using convergent series solution. Heat and mass transfer effects are carried out over numerically and graphically for various parameter of interest. According to the research, buoyancy and the mixed convection coefficient enhanced the x-component of velocity but decreased the y-component. The thermal and solutal energy transfers in the nanofluid were also improved by these two variables. It was also discovered that in the presence of the thermal relaxation phenomenon, the thermophoretic increased the flow's thermal energy transmission.